Examining the practices and success of community-based tourism: A study at Barru Regency, Indonesia - Junaid, Ilham (Masyarakat, Kebudayaan dan Politik, 2024)
Community-based tourism (CBT) is a way to encourage the community to get involved in tourism, and its success depends on the level of participation. Although many academics have discussed CBT, such a concept needs evaluation related to its implementation and how the community benefits. This paper aims to (1) identify the practices of CBT and factors affecting the conduct of beach tourism; (2) evaluate the success of CBT from the perspective of the local people. This paper employs the conceptual framework of success criteria for CBT by utilising qualitative data from in-depth interviews and observations at Ujung Batu Beach, Barru Regency. The research reveals that the practice of beach tourism consists of two, approaches: existing condition management and proposed people management. Six factors affect the conduct of tourism: boat parking by the fishermen, waste management, limited community participation, the natural condition of the coastal area, the existence of the local organisation and the availability of facilities. There should be more efforts to achieve the goals of CBT, including support from the coastal residents, promotion of uniqueness and environmental conservation. This paper contributes to advancing the knowledge of CBT from the perspective of beach tourism.